INNOVATION COUNSELING AND COUNSELING THROUGH BUDIKSAMBER PROGRAM IN PANDEMIC TIME COVID 19 (Economic Empowerment of the Bingluh Group in the Cipedes District, Tasikmalaya City) - Setiana, Agus; Suhada, Dodo; Ahyani, Hisam; Abduloh, Agus Yosep (Pusat Kajian Halal Undip, 2021)
ABSTRAKKebutuhan pangan merupakan sesuatu yang perannya sangat penting bagi masyarakat, apalagi di tengah-tengah pandemi seperti sekarang ini. Budiksamber sebagai salah satu program yang dicanangkan oleh komunitas Peduli Ketahanan Pangan Kota Tasikmalaya bekerjasama dengan Syahla Community ini bisa menjadi alternative untuk memenuhi kebutuhan pangan, terutama yang penghasilannya terdampak langsung oleh hadirnya Covid-19 ini. Inovasi yang dilakukan dalam mengatasi perekonomian di tengah-tengah pandemi covid 19 yakni melalui pemberdayaan pemanfaatan lahan disekitar rumah, yang mana dengan hadirnya Program Budiksamber sebagai bentuk Pemberdayaan Ekonomi Kelompok Bingluh di Kecamatan Cipedes Kota Tasikmalaya hadir memberi solusi dalam mengatasi perkenomian masyarakat, Manfaat dari program Budiksamber ini selain memperoleh ilmu dan pengalaman dalam pengelolaan budidaya ikan dan sayuran dalam ember, juga secara ekonomi dapat membantu mengurangi resiko biaya dapur. ABSTRACTThe need for food is something that plays a very important role for the community, especially in the midst of a pandemic like now. Budiksamber as one of the programs launched by the Tasikmalaya City Food Security Care community in collaboration with the Syahla Community can be an alternative to meet food needs, especially those whose income is directly affected by the presence of Covid-19. Innovations made in overcoming the economy in the midst of the COVID-19 pandemic, namely through empowering the use of land around the house, which with the presence of the Budiksamber Program as a form of Economic Empowerment for the Bingluh Group in Cipedes District, Tasikmalaya City, is here to provide solutions in overcoming community denominations, the benefits of the Budiksamber program In addition to gaining knowledge and experience in the management of fish and vegetable cultivation in buckets, it can also economically help reduce the risk of kitchen costs.